Dinamika Ekonomi Dan Adaptasi Nelayan Hand Line Terhadap Musim Pelagis Donggala - Ahsan Mardjudo; Hartina Hartina; Rusli Rusli; Sri Sudewi (Universitas Pattimura, 2026)
This study aims to examine the household economic dynamics and adaptation strategies employed by hand line fishers in response to seasonal changes affecting pelagic fish catches in Donggala Regency, Central Sulawesi. A total of 30 fishers operating from the Boneoge and Labuan Bajo landing sites were involved as respondents using a survey method with descriptive quantitative and qualitative approaches. The quantitative approach was applied to analyze differences in household income between the fishing season and the lean season using a paired-sample t-test. Meanwhile, the qualitative approach sought to explore in depth the various forms of socio-economic adaptation implemented by fishers due to seasonal changes in their fishing activities. Qualitative data were collected through in-depth interviews and field observations to understand household adaptation mechanisms, social networking practices, and the utilization of local institutions. The findings reveal that the average monthly household income of fishers declined sharply from IDR 5,790,000 during the fishing season to IDR 2,890,000 during the lean season, with a statistically significant difference (p < 0.05). This income reduction prompted fishers to adopt various adaptive strategies, including livelihood diversification, household financial management, and the strengthening of social ties among fishers. Household economic resilience was further supported by social adaptation practices based on mutual cooperation (gotong royong) and the use of local institutions. These results underscore that strengthening adaptive fisheries policies and socio-economically based management of pelagic fish resources is essential to enhance the adaptive capacity and livelihood sustainability of coastal communities.